Inhibition of adenylyl cyclase 1 by ST034307 inhibits IP3-evoked changes in sino-atrial node beat rate - Bose, Samuel J.; Read, Matthew J.; Akerman, Emily; Capel, Rebecca A.; Ayagama, Thamali; Russell, Angela; Terrar, Derek A.; Zaccolo, Manuela; Burton, Rebecca A. B. (Frontiers in Pharmacology, 2022)
Atrial arrhythmias, such as atrial fibrillation (AF), are a major mortality risk and a leading cause of stroke. The IP3 signalling pathway has been proposed as an atrial-specific target for AF therapy, and atrial IP3 signalling has been linked to the activation of calcium sensitive adenylyl cyclases AC1 and AC8. We investigated the involvement of AC1 in the response of intact mouse atrial tissue and isolated guinea pig atrial and sino-atrial node (SAN) cells to the α-adrenoceptor agonist phenylephrine (PE) using the selective AC1 inhibitor ST034307. The maximum rate change of spontaneously beating mouse right atrial tissue exposed to PE was reduced from 14.5% to 8.2% (P = 0.005) in the presence of 1 μM ST034307, whereas the increase in tension generated in paced left atrial tissue in the presence of PE was not inhibited by ST034307 (Control = 14.2%, ST034307 = 16.3%; P > 0.05). Experiments were performed using isolated guinea pig atrial and SAN cells loaded with Fluo-5F-AM to record changes in calcium transients (CaT) generated by 10 μM PE in the presence and absence of 1 μM ST034307. ST034307 significantly reduced the beating rate of SAN cells (0.34-fold decrease; P = 0.003) but did not inhibit changes in CaT amplitude in response to PE in atrial cells. The results presented here demonstrate pharmacologically the involvement of AC1 in the downstream response of atrial pacemaker activity to α-adrenoreceptor stimulation and IP3R calcium release.